If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 4 + -3(x + -1) = -3x + -1(4x + -1) + 3 Reorder the terms: -5x + 4 + -3(-1 + x) = -3x + -1(4x + -1) + 3 -5x + 4 + (-1 * -3 + x * -3) = -3x + -1(4x + -1) + 3 -5x + 4 + (3 + -3x) = -3x + -1(4x + -1) + 3 Reorder the terms: 4 + 3 + -5x + -3x = -3x + -1(4x + -1) + 3 Combine like terms: 4 + 3 = 7 7 + -5x + -3x = -3x + -1(4x + -1) + 3 Combine like terms: -5x + -3x = -8x 7 + -8x = -3x + -1(4x + -1) + 3 Reorder the terms: 7 + -8x = -3x + -1(-1 + 4x) + 3 7 + -8x = -3x + (-1 * -1 + 4x * -1) + 3 7 + -8x = -3x + (1 + -4x) + 3 Reorder the terms: 7 + -8x = 1 + 3 + -3x + -4x Combine like terms: 1 + 3 = 4 7 + -8x = 4 + -3x + -4x Combine like terms: -3x + -4x = -7x 7 + -8x = 4 + -7x Solving 7 + -8x = 4 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 7 + -8x + 7x = 4 + -7x + 7x Combine like terms: -8x + 7x = -1x 7 + -1x = 4 + -7x + 7x Combine like terms: -7x + 7x = 0 7 + -1x = 4 + 0 7 + -1x = 4 Add '-7' to each side of the equation. 7 + -7 + -1x = 4 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 4 + -7 -1x = 4 + -7 Combine like terms: 4 + -7 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| 13q-12q+q-2=12 | | 1.8x=.25 | | 100=x+10x | | 3x-3(4x+5)=-15 | | n-56=26 | | X^4+2x^2=6x^2 | | -13=3u-4 | | (4y+16)(4y+16)=8 | | 3-1x=6 | | 8e-4(12-5e)=60 | | 5b-6b-3=-11 | | -4(-h)=68 | | 5x-2(x-2)=-8+5x-2 | | 2f(x)=5x-7 | | 400000=x+.07x | | 30=5/6.w | | 9w-9w+w+3=15 | | x^2-12x+17.5=0 | | 5x+2y=x+4y | | -2/n=1.6/11.2 | | 3x-12x-15=15 | | M/-5=-5-18 | | 8x+12+x=180 | | 9r-5r-3r=20 | | 10=s-15 | | -3h-5=22 | | 5/7*2/3= | | 11z-2z+14z+-17z+-12z=12 | | 3x-9/6=4 | | Y=ax+bForx | | 3/4*3/8= | | 8w+12=9 |